Implementation of IOT Remote Control-Based Solar Panel Cleaning System Innovation on Mobile Tower - Riza, Febri Miftaqul; Batubara, Haris Fadhillah; Supriadi, Imam; Widiyanto, Agus; Yuko (Indonesian Journal of Multidisciplinary Science, 2025)
The use of solar panels as an alternative energy source in mobile towers is growing along with the increasing need for environmentally friendly energy. However, the build-up of dust and dirt on the surface of the solar panel can reduce energy efficiency by up to 15–30%. This research aims to implement an Internet of Things (IoT)-based solar panel cleaning system with remote control to overcome this problem. The system allows for automatic monitoring and control of panel cleaning remotely, reducing reliance on manual labor and operational costs. The results of the implementation show an increase in energy efficiency, cost savings, and a positive impact on environmental sustainability. These results have three key implications: (1) technical - proving IoT automation effectively maintains renewable energy systems; (2) economic - establishing a cost-effective alternative to manual maintenance; and (3) environmental - reducing diesel dependency by 40% at test sites. The solution offers telecom operators a scalable model for sustainable infrastructure maintenance, with potential applications in other remote solar installations. Future research should explore AI integration for predictive cleaning scheduling.